Results on frequency weighted model reduction techniques of activated sludge process - Sahlan, S. (2013)
In this paper, a 90th order activated sludge process system is explored. From the original high order system, a disturbance between 1rad/s to 10rad/s are observed, hence frequency weighted model reduction techniques (FWMRT) are applied with a low pass filter of break frequency 0.5rad/s. Three well-known techniques are utilized and compared to the original system on a sigma plot. The reduction techniques are Enn's, Wang et al's and Lin and Chiu's. Results show that the fourth order reduction yields good results whereby all techniques follow the original well, i.e. the characteristics performance of the original system is retained. Although Wang et al follow the original system very closely, Enn's technique is able to smooth out the disturbance and give good error approximation.